Inovasi Pendidikan Kewirausahaan untuk Mendorong Pertumbuhan Ekonomi Digital di Era Modern - Waroka, Linda Ardiya; Habiby, M. Nuril Anwar; Munadia, Munadia; Putri, Annisa; S, Nurjito A. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze innovations in entrepreneurship education to promote digital economic growth in the modern era. The study uses a Systematic Literature Review (SLR) approach to analyze innovations in entrepreneurship education in supporting digital economic growth. The reviewed papers are those published between 2020 and 2025, in Indonesian, and contain relevant keywords. The search process involves screening based on title and abstract, followed by an evaluation of the full text to ensure relevance and quality of information. Data from journals are synthesized to provide a comprehensive understanding of the topic. An analysis of ten articles shows that the development of entrepreneurship education is crucial to enhancing relevant skills in the digital era. This education not only provides technical knowledge but also encourages students to think creatively and independently. Although digital training offers many benefits, challenges such as the lack of teacher competencies and data privacy issues need to be addressed to ensure effective and safe implementation. This research emphasizes that entrepreneurship education is important for enhancing skills in the digital era. Students not only learn technical knowledge but are also trained to think critically and independently. Digital entrepreneurship training provides opportunities for the millennial generation to leverage technology.